Identification of appropriate indicators for assessing sustainability of small-holder milk production systems in Tanzania - Munyaneza, Celestin; Kurwijila, Lusato R.; Mdoe, Ntengua S.Y.; Baltenweck, Isabelle; Twine, Edgar E. (Elsevier, 2019)
Improving the economic, social and environmental sustainability of milk production in Tanzania requires relevant indicators to monitor its progress. There is no existing set of indicators to assess sustainability of smallholder dairy farming systems in Tanzania. This study was carried out to identify relevant indicators for assessing sustainability of smallholder dairy and traditional cattle milk production farms in Tanzania. In four districts, selected based on their potential in milk production, within two regions of Tanzania, a two-round Delphi approach involving 44 diverse experts and stakeholders was used. An “initial set” of 57 indicators was selected based on their relevance to the study context and measurability using literature review as well as discussions with experts and stakeholders. Then, the ‘initial set’ was refined to a final set of 29. The final set includes 18 indicators on economic, 4 on social and 7 on environment pillars. The key economic indicators were milk hygiene and cow productivity; social indicators were participation in organizations and women’s empowerment; environmental indicators were access to water and water conservation. The study showed that a large number of existing indicators might not be relevant in the context of Tanzania’s smallholder dairy and traditional cattle systems. The indicators identified here demonstrate the importance of matching any set of indicators to the characteristics and realities of the specific production system being examined. These indicators should help farmers and other stakeholders to monitor farm sustainability and guide decision makers to make appropriate policies for Tanzania.